A Case of COVID-19 Vaccine-Induced Thrombotic Thrombocytopenia. Issue 6 (2nd November 2021) - Chittal, Abhinandan; Rao, Shiavax; Lakra, Pallavi; Nacu, Natalia; Haas, Christopher
ABSTRACT: SARS-CoV-2, which originated in China in late 2019, has spread rapidly resulting in a global pandemic. Multiple vaccines have been developed to help prevent COVID-19 infection. Similar to other vaccines, common side effects including fever, fatigue, myalgias have occurred; however, episodes of more serious side effects have been noted. One such potentially serious sequalae is vaccine-induced thrombocytopenia (VITT), an autoimmune-mediated phenomenon hypothesized to occur due to molecular mimicry and the production of platelet PF4 antibodies, ultimately leading to thrombocytopenia and easy bruising. In this report, we present the case of a 34-year-old, otherwise, healthy female who presented with easy bruising and thrombocytopenia following completion of the two-dose Moderna COVID-19 vaccine, suspicious for a diagnosis of VITT. The patient was managed conservatively with steroids. Steroids and intravenous immune globulin therapy have been reported in the literature. This report highlights that VITT should be considered in the differential diagnosis for patient presenting with increased bruising in the setting of recent COVID-19 vaccine administration, and furthermore highlights the diagnostic workup and management options for such patients.